Mechanical stability of substrate-bound graphene in contact with aqueous solutions. (18th May 2015) - Velický, Matěj; Cooper, Adam J; Toth, Peter S; Patten, Hollie V; Woods, Colin R; Novoselov, Konstantin S; Dryfe, Robert A W
Abstract: We report on the damage caused to mechanically exfoliated monolayer graphene, bound to silicon dioxide substrate, upon contact with liquids. This phenomenon is of significant importance for a wide range of applications where monolayer graphene sheets are used with liquids, especially as an electrode material in electrochemical applications such as energy storage and conversion. Liquid-induced damage to SiO2 -bound graphene was previously observed with a range of solvents. A recently developed microdroplet system, used for a detailed examination of this behaviour, reveals that few-layer graphene flakes down to a bi-layer are stable with respect to aqueous electrolyte droplet formation, but the stability of these droplets is significantly reduced on monolayer graphene and irreversible rupture of the underlying graphene flake occurs. This damage, which we attribute to the presence of nanoscale defects and high adhesion between the graphene and the substrate, seems specific to plasma-cleaned SiO2 substrates and is not observed on flakes transferred to other substrates. Furthermore, the introduction of impurities, in the form of both polymer residues and native impurities between the flake and the SiO2 substrate, significantly enhance graphene's immunity to external strain as shown by optical microscopy, atomic force microscopy, and Raman spectroscopy.